Some kinds of sparseness on the real line and ideals on ω - Filipczak, Małgorzata; Horbaczewska, Grażyna (Annales Mathematicae Silesianae, 2020)
We show that a large class of summable ideals can be defined using a certain kind of “sparseness” of subsets of the line near zero, but it is still an open question whether this gives a characterization of the whole class.